Enhancing 11th Graders’ Reading Comprehension by Using Making Connection Technique - Nafisya Alfiani Aisyah; Nur Fajar Arief (EDUTEC : Journal of Education And Technology, 2021)
Reading is a comprehending process that involves complex steps. Despite the important role of reading comprehension, many researchers indicate that the students’ reading comprehension skill is not satisfactory yet. This situation is also found in MAN 3 Malang. The students were found to have difficulty in comprehending the reading text because of low ability in reading, especially in drawing on their prior knowledge. Thus, the researcher implemented the Making Connection Technique in the reading lessons in collaboration with the classroom teacher. This technique has several steps; they are text to text, text to self, and text to world. The design of this research was Classroom Action Research covering four stages; they were planning, implementing, observing, and reflecting. The subjects of the study were 29 students of class XI SCIENCE 1 of MAN 3 Malang. The instruments used to collect the data were students’ reading comprehension pre and post-test), observation checklist, and field notes. Since the researcher aimed to know whether the technique helped the students in both the lower and upper groups, this research is successful if there was a significant improvement from their pre and post-test scores. The findings of this study revealed that by using the Making Connection technique, the student's reading comprehension scores had achieved the criteria of success. The students also showed a positive attitude during the implementation of the technique. The several procedures of using the technique found are (1) making text to text-connection in the group, (2) making text to self-connection in the group, (3) making text to world-connection in the group, and (4) having a class discussion related to the results of their discussion. Based on the research findings, the researcher suggested English teachers to implement the making connection technique in more interesting ways. Future researchers can investigate the use of making connection technique for other research purposes